2001
DOI: 10.1002/cne.1287
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐immunoreactive neurons in the mushroom bodies of the honeybee: An electron microscopic study

Abstract: Synaptic contacts of gamma-aminobutyric acid (GABA) -immunoreactive neurons in honeybee mushroom bodies were studied by using electron microscopic immunocytochemistry. In the lip region of the calyx neuropil, GABA-immunoreactive profiles formed synapses onto both small postsynaptic profiles (76%) and large immunonegative boutons (4%), which were likely to belong to the intrinsic and extrinsic mushroom body neurons, respectively. Three morphologic types of the large immunonegative boutons were distinguished: "l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(187 citation statements)
references
References 55 publications
8
171
3
1
Order By: Relevance
“…In honey bees, these neurons have been proposed to function as an inhibitory feedback loop (Grünewald, 1999b;Ganeshina and Menzel, 2001). Such differences between hemi-and holometabolous insects regarding the dendritic placement of GABAimmunoreactive neurons suggest that there may have been an evolutionary change from the basal (hemimetabolous) condition, where dendrites of GABA-immunoreactive neurons supplying the calyces were originally located in protocerebral areas outside the pedunculus and lobes.…”
Section: Discussionmentioning
confidence: 99%
“…In honey bees, these neurons have been proposed to function as an inhibitory feedback loop (Grünewald, 1999b;Ganeshina and Menzel, 2001). Such differences between hemi-and holometabolous insects regarding the dendritic placement of GABAimmunoreactive neurons suggest that there may have been an evolutionary change from the basal (hemimetabolous) condition, where dendrites of GABA-immunoreactive neurons supplying the calyces were originally located in protocerebral areas outside the pedunculus and lobes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that synaptic complexes in MB calyces both from Drosophila and in honeybees, present a typical ring-like shape (34)(35)(36)(37). To test whether DenMark is indeed present at these ring-like synaptic structures, we labeled the presynaptic terminals by revealing ChAT (Choline Acetyl Transferase) immunoreactivity.…”
Section: J)mentioning
confidence: 99%
“…Others had no obvious morphological defects. From these groups (29,30,31, and 37°C), only those bees with no apparent morphological defects were used for neuroanatomical analyses.…”
Section: Temperature Dependence Of Emergence Rate and Duration Of Pupalmentioning
confidence: 99%
“…1 C-E and M). These microglomeruli (MG) represent distinct synaptic complexes in the calyx neuropil, each comprising a central bouton from PN axons surrounded by many KC dendritic spines and processes from other extrinsic neurons (27,(29)(30)(31). Synapsin-IR, which is associated with synaptic vesicles, stained the central bouton of MG, whereas phalloidin labeled a ring-like surrounding region ( Fig.…”
Section: Temperature Dependence Of Emergence Rate and Duration Of Pupalmentioning
confidence: 99%